Estudio de creación de una microempresa Industrial Productora de Harina con Proteína a base de Soya en la Parroquia de Cacha-Riobamba - Bolaños Donoso, Bryan Marcelo (2022)
This research work deals with the feasibility study for the creation of a microenterprise producing flours added with soy in the parish of Cacha. In the first instance, the possible market segment was identified, determining through surveys a 31.5% acceptance rate for the product máchica flour with soy and a 26.5% acceptance for the corn flour product with soy with a sales projection for the first year of 254429 pounds of Máchica Flour with Soy and 173284 pounds of Corn Flour with Soy, these values represent 30% of the total demand having a reference price of $1.50 per pound. In the technical study, the most accepted concentration was determined through tasting surveys to the target market that are the families, in addition, the plant design was elaborated specifying the production process, raw material and machinery necessary for the elaboration of the product. In the administrative study, the functional organizational structure, the mission and functions of the position were established for each of the workers who will integrate the work team, finally a total investment of $318,687.45 was determined through the financial study, a Minimum Acceptable Rate of Return (TMAR) of 10.35%, a 15% Net Present Value (NPV) of $68,293.15, an Internal Rate of Return (IRR) of 28.33%, a Cost Benefit (C/B) of $1.31 a Net Present Value of 15% (NPV) indicating that for every dollar invested $0.31 will be earned, the Payback Period (PRC) is of 4 years, 1 month and 13 days, being the feasible project for its execution.